Analisis Tindak Tutur Imperatif dalam Pembelajaran Bahasa Daerah Kelas Sekolah Menengah - Anindia Dila Lana Putri; Asia M.; Syamsudduha Syamsudduha (HUMAN: South Asian Journal of Social Studies, 2022)
Abstract: Imperative Speech Acts Analysis in Regional Language Learning Class VIII SMP Negeri 1 Tarowang. Thesis of Regional Language and Literature Education Study Program, Department of Indonesian Language and Literature, Faculty of Language and Literature, Makassar State University. This study aims to describe the form of speech acts and forms of imperative speech of teachers and students in learning regional languages for class VIII SMP Negeri 1 Tarowang by using the theory guide of Kunjana Rahardi. The analysis in this study is a qualitative descriptive study. The techniques used in data collection were observation techniques, video recording techniques, note-taking techniques, and documentation techniques and listening techniques. Analysis of how to observe, record, clarify, and classify the data obtained. Then draw conclusions. The results showed that the form of speech acts and the form of imperative speech obtained consisted of eleven forms, namely 1) imperative imperative of nine speech forms, 2) imperative imperative of asking for four forms of speech, 3) imperative of requesting of six forms of speech, 4) imperative of insisting on five forms of speech, 5 ) imperative of persuading two speech forms, 6) imperative of inviting three forms of speech, 7) imperative of allowing three forms of speech, 8) imperative of prohibiting six forms of speech, 9) imperative of wishing for two forms of speech, 10) imperative of congratulating three forms of speech and 11 ) imperative suggesting three forms of findings. Keywords: Imperative speech, teacher, student, regional language